(untitled) (Journal of the College of Basic Education, 2024)
The objective of the current research is to identify Bransford & Stein’s model in mathematics. A sister sample The research sample was intentional and was represented by the students of the second intermediate grade in the Dijla Secondary School for Girls, affiliated to the General Directorate of Kurdish Education. The school contains four divisions for the second intermediate grade, which are (A, B, C, D(Two divisions were chosen randomly, as division (A) was chosen to represent the experimental group that will be taught using (Bransford & Stein’s) model with (30) female students, and division (C) to represent the control group that will be taught in the usual way with (30) female students, After excluding the (3) female students from the two groups, the number of female students in the sample became (60) female students, with (30) female students in the experimental group and (30) female students in the control group. previous mathematics achievement, and chronological age) The experiment was conducted in the first semester of the academic year (2022-2023), and the researcher adopted the experimental approach. The lateral thinking test was prepared as a research tool. The lateral thinking test was prepared, as it consisted of (25) items, including (13) objective items and (12) items. For an essay paragraph, the researcher calculated the stability of the test and its skills using the (Cronbach’s alpha) equation, which is suitable for the objective paragraphs. for two independent samples and a test (Levenes’ test(The results showed that there are statistically significant differences between the experimental and control groups in the lateral thinking test in favor of the experimental group. Applying lateral thinking skills and integrating them into the educational process intensively because they are directly reflected in their learning in the scientific subject, in addition to applying them in reality. She suggested conducting a comparison study between Bransford & Stein’s model and other models, to show which is more effective in lateral thinking skills.